How Does Mentoring Affect Protégés’ Adaptive Performance in the Workplace: Roles of Thriving at Work and Promotion Focus - Zeng, Hao; Zhao, Lijing; Ruan, Shuai (Frontiers in Psychology, 2020)
The question of how to improve employees’ adaptive performance in dynamic environments has become a hot issue in organizational management. Although previous research has focused on the antecedents of adaptive performance, less attention has been paid to the impact of mentoring. Based on the conservation of resources theory and regulatory focus theory, this study examines the impact mechanism and boundary conditions of mentoring on protégés’ adaptive performance. In addition, through an empirical analysis of 269 samples, this study finds that mentoring has a significant positive impact on protégés’ adaptive performance. Thriving at work plays a full mediation role between mentoring and protégés’ adaptive performance, and protégés’ promotion focus moderates the relationship between mentoring and thriving at work such that the relationship is stronger among protégés with a higher promotion focus. Furthermore, the indirect relationship between mentoring and adaptive performance is stronger when protégés have a high level of promotion focus.